Spectators - Vaughan, Brian K. (Image Comics, 2025)
"Hundreds of years in the future, New York City is haunted by many ghosts, including a voyeuristic woman who died in our present day and a mysterious gun-toting man from the distant past. Normally solotravelers, these two specters meet and travel around the world together, bearing witness to society's forward march toward decay. A gripping and provocative graphic novel that takes a hard look at sex and violence, and the very different ways we obsessively watch both."--Provided by publisher.